Ischemic Postconditioning-Mediated DJ-1 Activation Mitigate Intestinal Mucosa Injury Induced by Myocardial Ischemia Reperfusion in Rats Through Keap1/Nrf2 Pathway - Chen, Rong; Li, Wei; Qiu, Zhen; Zhou, Qin; Zhang, Yuan; Li, Wen-yuan; Ding, Ke; Meng, Qing-tao; Xia, Zhong-yuan (Frontiers in Molecular Biosciences, 2021)
Intestinal mucosal barrier dysfunction induced by myocardial ischemia reperfusion (IR) injury often leads to adverse cardiovascular outcomes after myocardial infarction. Early detection and prevention of remote intestinal injury following myocardial IR may help to estimate and improve prognosis after acute myocardial infarction (AMI). This study investigated the protective effect of myocardial ischemic postconditioning (IPo) on intestinal barrier injury induced by myocardial IR and the underlying cellular signaling mechanisms with focus on the DJ-1. Adult SD rats were subjected to unilateral myocardial IR with or without ischemic postconditioning. After 30 min of ischemia and 120 min of reperfusion, heart tissue, intestine and blood were collected for subsequent examination. The outcome measures were: (i) intestinal histopathology; (ii) intestinal barrier function and inflammatory responses; (iii) apoptosis and oxidative stress and (iv) cellular signaling changes. IPo significantly attenuated intestinal injury induced by myocardial IR. Furthermore, IPo significantly increased DJ-1, nuclear Nrf2, NQO1 and HO-1 expression in the intestine and inhibited IR-induced apoptosis and oxidative stress. The protective effect of IPo was abolished by knockdown of DJ-1. Conversely, overexpression of DJ-1 provided a protective effect similar to that of IPo. Our data indicate that IPo protects the intestine against myocardial IR, which is likely mediated by upregulation of the DJ-1/Nrf2 pathway.